Teacher satisfaction with school and psychological well-being affects their readiness to help children with mental health problems: $hMerike Sisask, Peeter Värnik, Airi Värnik, Alan Apter, Judit Balazs, Maria Balint, Julio Bobes, Romuald Brunner, Paul Corcoran, Doina Cosman, Dana Feldman, Christian Haring, Jean-Pierre Kahn, Vita Poštuvan, Alexandra Tubiana, Marco Sarchiapone, Camilla Wasserman, Vladimir Carli, Christina W. Hoven and Danuta Wasserman - Sisask, Merike; Brunner, Romuald (The Health education journal, 2014)
Objective: In support of a whole-school approach to mental health promotion, this study was conducted to find out whether and how significantly teachers’ satisfaction with school and their subjective psychological well-being are related to the belief that they can help pupils with mental health problems. Design: Cross-sectional data were collected as a part of the European Union’s, Seventh Framework Programme for Research (FP7) Saving and Empowering Young Lives in Europe (SEYLE) study. One of the elements of the SEYLE study was to evaluate teachers’ attitudes and knowledge related to pupils’ mental health issues and their own psychological well-being, as well as their satisfaction with the school environment. Setting: The sample of schools from the SEYLE study sites representing 11 European countries was randomly chosen according to prior defined inclusion and exclusion criteria. The final cross-sectional database used for analysis in the current study comprised 2485 teachers from 158 randomly selected schools. Method: Respondents’ belief that teachers can help pupils with mental health problems served as the outcome variable in our predictions with probability of the positive answer being modelled in the logistic regression analysis. Teachers’ subjective psychological well-being and school satisfaction were included as independent variables in the logistic regression model and several other relevant variables were added to statistically control for them. Multiple models were tested in order to obtain the final model. Results: Logistic regression models showed that better satisfaction with general school climate, higher psychological well-being, and the ability to understand pupils’ mental health problems increased the odds of teachers’ readiness to help pupils with mental health problems. Conclusion: By providing a good school environment, by valuing the subjective psychological well-being of the teachers, and by providing adequate training to fulfil their ‘gatekeeper’ role, the preconditions to improve the mental health of the pupils they teach will be achieved. These suggestions are in line with a whole-school approach to mental health promotion.